The sleep quality and influencing factors among midwives in China: a cross-sectional study - Dongning He; Dongning He; Jinling Zhang; Jinling Zhang; Mingxin Zhu; Mingxin Zhu; Yangxue Meng; Yangxue Meng; Na Li; Na Li; Guoyu Wang; Guoyu Wang; et al. (Frontiers in Public Health)
ObjectiveThis study aimed to assess sleep quality and identify influencing factors among midwives in mainland China, providing a reference for obstetric managers to develop strategies that enhance sleep health among midwives.MethodsThe study was conducted from January to December 2023 across 566 hospitals in mainland China. A total of 1,948 midwives participated. A self-designed questionnaire was used to collect socio-demographic information and participants' perceived factors influencing their sleep quality. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), and regression analysis was performed to identify the factors influencing sleep quality.ResultsThe median Pittsburgh Sleep Quality Index score was 9, with 71.9% (n = 1,400) of midwives reporting poor sleep quality (cutoff score >7). Additionally, 12.4% of midwives required medication to assist with sleep. Statistically significant differences (P < 0.05) in scores were observed across variables such as years of experience as a midwife, health status, hospital type, work mode, ability to leave work on time, and sleep assistance situation. Regression analysis indicated that health status, hospital type, work mode, ability to leave work on time, the need for sleep assistance, and perceived work pressure were significant factors influencing sleep quality among midwives.ConclusionThe overall sleep quality of Chinese midwives is poor, influenced by both work-related and individual factors. Obstetric managers should allocate clinical staff and resources efficiently. This can be achieved by adjusting shift rotations, reducing overtime, and implementing other measures to create an environment that supports better sleep quality among midwives, enhancing their work performance and ensuring maternal and neonatal safety.